The formation of a lawyer as a challenge of times - Stadniczeńko, Stanisław Leszek (The Opole Studies in Administration and Law, 2017)
The author considers the questions relating to the formation of lawyers’ professional traits from the point of view of the significance which human capital and investment in this capital hold in contemporary times. It follows from the analyses, which were carried out, that the dire need for taking up actions with the aim to shape lawyers appears one of the most vital tasks. This requires taking into account visible trends in the changing job market. Another aspect results from the need for multilevel qualifications and conditions behind lawyers’ actions and their decisions. Thus, colleges of higher education which educate prospective lawyers, as well as lawyers’ corporations, are confronted by challenges of forming, in young people, features that are indispensable for them to be valuable lawyers and not only executors of simple activities. The author points to the fact that lawyers need shaping because, among others, during their whole social lives and realization of professional tasks their personality traits and potential related to communication will constantly manifest through accepting and following or rejecting and opposing values, principles, reflexions, empathy, sensitivity, the farthest-fetched imagination, objectivism, cooperation, dialogue, distancing themselves from political disputes, etc. Students of the art of law should be characterized by a changed mentality, new vision of law – service to man, and realization of standards of law, as well as perception of the importance of knowledge, skills, attitudes and competences.